Textos motivadores do Enem, da Fuvest e do Mackenzie: uma análise retórica das propostas de redação - Araújo, Carlos Henrique Teixeira de (2020)
From the analysis of a collections of entrance exam texts to guide the text production in the entrance examination of Enem (2009 and 2018), of Fuvest (2009 and 2018) and of Mackenzie Presbyterian University (2009 and 2018), this master’s thesis, through a rhetoric analysis, aims at describing and analyzing the existent and available argumentative procedures in the motivating texts chosen by the described institutions to set forth or to direct the subject of discussion to be considered in the text production exam as a way to access the higher education. In a more specific term, the research method and its procedures contemplate analytical examination of the types of arguments and rhetorical resources applied and prevalent in the motivating texts in terms of to present a base from which candidates could elaborate their own writing in the text production test. The undertaken rhetorical analysis found support on the fundamentals of Text Linguistic and Discourse Analysis, to the extent that it considers persuasion as a text and a discursive component current in rhetorical discourses, in which gets in interaction auditorium and speaker. It was noticed through the analysis that there is a stability in the genre – motivating texts in the entrance exam – with the presence of style, operation and structural organization, despite the temporal distance encompassed by the material selected for analysis. An interpretative synthesis, besides mapping the most applied argumentative strategies in order to obtain effectiveness in persuasion and to set the argumentative direction to be taken by the candidates in the exam, points to a reflection concerning working with text in secondary education which also includes the languages’ rhetorical component.